Effects of prestressing and saw-cutting on the freeze-thaw durability. (November 2019) - Albahttiti, Mohammed T.; Ghadban, Ahmad A.; Riding, Kyle A.; Lange, David A.
Abstract: There are many factors that affect the freeze-thaw durability of concrete elements, including proper air entrainment system, freeze-thaw durable aggregates, low permeability, and proper curing. While ASTM C666 allows the excising of small freeze-thaw samples from larger sections it doesn't address the issues that can arise when excising samples from prestressed concrete and subsequent testing in freezing and thawing. In order to investigate the effects of saw-cutting, the existence of reinforcement, and use of prestressing, concrete samples of different sizes, with and without saw-cutting, with and without reinforcement, and with and without prestressing were tested in freeze-thaw. The freeze-thaw mechanism was adjusted, from that of ASTM C666, for the larger sample in terms of freezing and thawing rates and the testing method. The results indicate that saw-cutting through plain concrete had minimal effect on the freeze-thaw durability, whereas sawcuts through reinforcement were shown to be very detrimental to the measured durability in the tests.